2018
DOI: 10.3324/haematol.2018.199414
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of plerixafor dose escalation for the mobilization of CD34+ hematopoietic progenitor cells in patients with sickle cell disease: interim results

Abstract: An incorrect version of sentence appared on May 2018 Issue, pages 773.Our target goal of mobilizing at least 30 CD34 + cells/μL was, however, reached in only 50% of patients given the plerixafor dose of 80 μg/kg, 33% of patients given 160 μg/kg, and 33% of patients given 240 μg/kg. The corrected version of sentence is published below.Our target goal of mobilizing at least 30 CD34 + cells/μL was, however, reached in only 50% of patients given the plerixafor dose of 80 μg/kg, 67% of patients given 160 μg/kg, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…In 2016, the HGB‐206 protocol was modified for Group B to increase DP vector copy number (VCN), require preharvest transfusions, increase target busulfan levels, and in Group C, explore the use of plerixafor for mobilization and apheresis for cell collection. Reports suggest higher CD34 + cells/kg yield after plerixafor mobilization, improved transduction efficiency, and improved HSC quality compared to BM from subjects with SCD (Uchida et al , ; Tisdale et al , ; Boulad et al , ; Esrick et al , ; Lagresle‐Peyrou et al , ; Leonard et al , ). In HGB‐206, a median CD34 + yield was reported of 4·3 (0·1–10·8) × 10 6 and 10·4 (3·8–21·6) × 10 6 cells/kg (Mapara et al , ).…”
Section: Clinical Gene Therapy Results In Sickle Cell Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, the HGB‐206 protocol was modified for Group B to increase DP vector copy number (VCN), require preharvest transfusions, increase target busulfan levels, and in Group C, explore the use of plerixafor for mobilization and apheresis for cell collection. Reports suggest higher CD34 + cells/kg yield after plerixafor mobilization, improved transduction efficiency, and improved HSC quality compared to BM from subjects with SCD (Uchida et al , ; Tisdale et al , ; Boulad et al , ; Esrick et al , ; Lagresle‐Peyrou et al , ; Leonard et al , ). In HGB‐206, a median CD34 + yield was reported of 4·3 (0·1–10·8) × 10 6 and 10·4 (3·8–21·6) × 10 6 cells/kg (Mapara et al , ).…”
Section: Clinical Gene Therapy Results In Sickle Cell Diseasementioning
confidence: 99%
“…With regard to gene therapy, success is dependent on safely obtaining a sufficient quantity of autologous SCD patient HSCs capable of lifelong engraftment. In patients with SCD, steady‐state BM harvesting is associated with suboptimal HSC quality and yield (Leonard et al , ), and PB mobilization with granulocyte colony stimulating factor is contra‐indicated (Abboud et al , ; Adler et al , ; Fitzhugh et al , ) though single‐agent plerixafor mobilization appears to be safe and effective (Tisdale et al , ; Boulad et al , ; Esrick et al , ; Lagresle‐Peyrou et al , ). Some patients may be unable to tolerate stem cell collection due to high risk of anaesthesia and fluid shifts in a BM harvest or PB collection.…”
Section: Haploidentical Transplantation Versus Gene Therapymentioning
confidence: 99%
“…All subsequent study procedures in both arms were in accordance with our institutional guidelines, following a commonly used dose-escalation algorithm. 4 Participants were deemed to be at MTD if their ANC was between 1.0-3.0 × 10 9 /L or ARC was between 80-100 × 10 9 /L on two sequential clinic visits at least a month apart on a stable hydroxyurea dose. Determination of MTD was made by the participantʼs primary clinician and the study primary investigator using the criteria described above.…”
Section: Supporting Informationmentioning
confidence: 99%
“…2 Single-agent plerixafor, instead of G-CSF, has recently been described as a safe and effective alternative for HSPC mobilization in SCD. 1,[3][4][5] Here, we report results from the first multi-center experience of collecting HSPCs for gene therapy manufacture by apheresis post-mobilization with a single-daily dose of plerixafor compared with BMH.…”
mentioning
confidence: 99%
“…In the case of autologous donors with sickle cell disease, G‐CSF injections are contraindicated due to the risk of precipitating potentially life‐threatening pain crises . Instead, a single injection of subcutaneous plerixafor alone (180‐240 μg/kg) is administered 4 to 6 hours before starting apheresis . In donors with suboptimal yields, a second day apheresis with a repeat dose of plerixafor, using a deep collection interface, may improve HPC yields .…”
Section: Apheresis Collectionmentioning
confidence: 99%